2015
DOI: 10.3906/sag-1307-44
|View full text |Cite
|
Sign up to set email alerts
|

What primary care physicians think about insulin initiation in type 2 diabetes:a field-based study

Abstract: Background/aim: A significant number of patients with type 2 diabetes mellitus require insulin and little is known about the possible physician-related factors that could cause a delay in the initiation of insulin treatment in patients with type 2 diabetes. This study aimed to evaluate those factors.Materials and methods: A total of 87 family physicians working at 36 family health centers in urban Malatya participated in our study on a voluntary basis. A self-administered survey form was structured to gather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As patient training is critical regarding DM follow-up and treatment, we believe that primary care physicians should provide guidance tailored to individual patient needs; multidisciplinary teams including nurses and specialists working in primary care clinics have successfully increased the initiation levels of insulin therapy. [24] The DM patients of the cited study stated that they commenced insulin therapy because their physicians gave them confidence, and explained how insulin worked. Insulin acceptance studies have shown that DM patients who refused insulin lacked knowledge on what insulin achieved.…”
Section: The Knowledge About Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…As patient training is critical regarding DM follow-up and treatment, we believe that primary care physicians should provide guidance tailored to individual patient needs; multidisciplinary teams including nurses and specialists working in primary care clinics have successfully increased the initiation levels of insulin therapy. [24] The DM patients of the cited study stated that they commenced insulin therapy because their physicians gave them confidence, and explained how insulin worked. Insulin acceptance studies have shown that DM patients who refused insulin lacked knowledge on what insulin achieved.…”
Section: The Knowledge About Insulinmentioning
confidence: 99%
“…Insulin acceptance studies have shown that DM patients who refused insulin lacked knowledge on what insulin achieved. [24] It is common for DM patients to lack information on insulin, or to be misinformed when insulin is first recommended. [25] Most DM patients manage their disease poorly and do not understand the significance of their condition or the effects of treatment.…”
Section: The Knowledge About Insulinmentioning
confidence: 99%